2009
DOI: 10.1245/s10434-008-0180-z
|View full text |Cite
|
Sign up to set email alerts
|

A Proposed Staging System for Intrahepatic Cholangiocarcinoma

Abstract: The American Joint Committee on Cancer (AJCC)/International Union Against Cancer (UICC) staging system for liver cancer is based on data exclusively derived from hepatocellular carcinoma (HCC) patients and thus may be inappropriate for patients with intrahepatic cholangiocarcinoma (ICC). We sought to empirically derive an ICC staging system from population-based data on patients with ICC. The Surveillance, Epidemiology, and End Results (SEER) database was used to identify 598 patients who underwent surgery for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

8
292
1
7

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 292 publications
(308 citation statements)
references
References 32 publications
8
292
1
7
Order By: Relevance
“…19 It is largely based on an analysis of data extracted from the Surveillance, Epidemiology and End Results (SEER) program on 598 patients who had undergone cancer-directed surgery for IHCC. 18 These patients were found to be inaccurately differentiated by the 6th edition of the AJCC as well as by both Japanese systems. In particular, a monotonicity of gradients was not observed.…”
mentioning
confidence: 96%
See 2 more Smart Citations
“…19 It is largely based on an analysis of data extracted from the Surveillance, Epidemiology and End Results (SEER) program on 598 patients who had undergone cancer-directed surgery for IHCC. 18 These patients were found to be inaccurately differentiated by the 6th edition of the AJCC as well as by both Japanese systems. In particular, a monotonicity of gradients was not observed.…”
mentioning
confidence: 96%
“…16 Although largely validated worldwide for HCC, 17 it has proven reliable when applied to patients with IHCC. 9,18 Therefore, the 7th edition of the AJCC staging manual, which takes effect this year, has for the first time proposed a novel staging specific to IHCC. 19 It is largely based on an analysis of data extracted from the Surveillance, Epidemiology and End Results (SEER) program on 598 patients who had undergone cancer-directed surgery for IHCC.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1 ICC accounts for 5-30% of all primary liver malignancies, and its incidence has been increasing over the last several decades. 2 The mortality from intrahepatic cholangiocarcinoma is very high, with the 5-year survival rates being o15-20% in most series. 3,4 However, the exact molecular mechanisms of biliary epithelium malignant transformation are not well understood.…”
mentioning
confidence: 99%
“…15 In 2010, the 7th edition of the American Joint Committee on Cancer (AJCC 7th) issued a new staging system for ICC based on data from the Surveillance, Epidemiology and End Results (SEER) program on almost 600 patients, who had undergone surgical resection. 14,22 Analysis included 15-year resection data out of 12 tertiary hepatobiliary centers with 168 R0 (no residual tumor) patients. Analysis of data demonstrated that N0M0 patients had 1-year and 5-year median survival rate of almost 90% and 44% respectively.…”
mentioning
confidence: 99%